ATTITUDE OF FARMERS TOWARDS ADOPTION OF RURAL WATER SANITATRY PRACTICES AMONG FARMERS IN PLATEAU STATE NIGERIA - Dodo, E.Y.; Dikko, U.R. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted to determine attitude of farmers towards adoption of rural water sanitary practices among farmers in Plateau state Nigeria. Nigeria. A multistage sampling procedure was used to select sample size of 279. Data were collected using structured questionnaire and analyzed using descriptive statistics. Findings revealed that average household size was about 7 people with mean income of about N454, 000.00 per annum. The respondent attended formal education at various levels It was further observed that, adoption of storage of water in clean containers had the highest adoption. On the attitudes of respondents to RUWASA recommended practices, findings revealed that only 30% of farmers generally had positive attitudes towards RUWASA recommended practice. This was precipitated by high percentage of people with RUWASA related diseases in the previous one-year, inadequate water usage, low percentage of people with appropriate hand washing behaviour and also low percentage of people with access to and proper use of toilets/latrines which were 30%, 37 lcd, 8% and 15% respectively against the international standards of 25%, 50Lcd 50% and 75% respectively for the same recommended practices. Based on the finding of this study, it was recommended that there is need for sustained efforts in educating farmers on the dangers of non-adherence to RUWASA recommended practices and also legislation in the local government council’s by-laws is necessary to enforce compliance.